Legitimation analysis: exploring decision-making and power in Hot Bench - Mohd Muzhafar Idrus,; Nor Fariza Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Research in discourse analysis has demonstrated that power can be illuminated through analyzing discourses. Centered on the notion that power and legitimation go hand-in-hand, these discourses are distinguished by specific linguistic components. One of the ways to explore how legitimation is tranquilized is to scrutinize its discourses, which some scholars (Wang, 2006; Van Leeuwen, 2007) argue have the precedence to control some of everyday, social, and public spheres. Following this premise, this paper examines how legitimation is jostled in selected decision-making scenes in a popular syndicated three-judge panel TV court show, Hot Bench. Two objectives are set out for this study; firstly to examine how organization and resolution of cases are generally settled and secondly to identify the types of legitimation employed by the judges in their decision-making processes. Premiered in 2014, Hot Bench draws over 2 million viewers in October 2014, jumping to a staggering 2.5 million viewers in November 2014, emerging as one of the most watched syndicated legal reality TV programs in United States of America with its second season renewed through 2017. By analyzing selected conversations by judges who deliberate verdicts, this study which employs Van Leeuwen’s framework of legitimation concludes that the judges typically employ three types of legitimation, namely, authorization, moral evaluation, and rationalization over the course of adjudicating TV’s court proceedings. This study ultimately contributes to the broader field of discourse analysis by tapping onto the belief that language, through discourse analysis, serves as a vehicle within which specific discourse community maintains power.